Continuous photo-oxidation of methane to methanol at an atomically tailored reticular gas-solid interface - Yuchen Hao; Liwei Chen; Haodong Liu; Wenfeng Nie; Xiangjie Ge; Jiani Li; Hui-Zi Huang; Chao Sun; Cuncai Lv; Shangbo Ning; Linjie Gao; Yaguang Li; et al. (Nature Communications)
Abstract Photo-oxidation of methane (CH4) using hydrogen peroxide (H2O2) synthesized in situ from air and water under sunlight offers an attractive route for producing green methanol while storing intermittent solar energy. However, in commonly used aqueous-phase systems, photocatalysis efficiency is severely limited due to the ultralow availability of CH4 gas and H2O2 intermediate at the flooded interface. Here, we report an atomically modified metal-organic framework (MOF) membrane nanoreactor that promotes direct CH4 photo-oxidation to methanol at the gas-solid interface in a reticular open framework. We show that the domino synergy between colocalized single-atom palladium and iron on MOF nodes enables efficient generation and in situ utilization of H2O2 in the absence of liquid water, thus circumventing H2O2 dilution. Meanwhile, the “breathable” MOF membrane, optimized by solar-driven interfacial water management, provides high-flux channels to facilitate efficient gas diffusion and rapid methanol desorption and transfer. As a result, we demonstrate over 210 hours of continuous photosynthesis of 0.25 M methanol with unity selectivity, achieving an exceptional methanol productivity of 14.4 millimoles per gram of catalyst per hour.